2022
DOI: 10.1002/ente.202200197
|View full text |Cite
|
Sign up to set email alerts
|

Sb‐Substituted Cs2AgBiBr6—As Much As It Could Be?—Influence of Synthesis Methods on Sb‐Substitution Level in Cs2AgBiBr6

Abstract: silicon solar cell. [3][4][5][6] Pb-based halide perovskites have shown remarkable and unique PV properties compared to silicon such as tunable bandgaps, high optical absorption coefficients, balanced effective masses of electrons and holes, longer diffusion lengths, extended lifetimes of the photogenerated charge carriers, and smaller exciton binding energies. [7][8][9] Facile fabrication technology with high defect tolerance is another advantage in Pb-based halide perovskites. However, a major problem to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…51 Nevertheless, due to the high formation energy of Cs 2 AgSbBr 6 and considering the small ionic radius of Sb 3+ relative to Bi 3+ , synthesizing Cs 2 AgBiBr 6 powdered samples with a high level of Sb substitution is a challenging task. 47,52 In a single photocatalyst, rapid charge recombination is dominant because of the extraordinarily strong coulombic force between photogenerated electrons and holes, leading to low photoactivity. This issue can be addressed by coupling the material with another semiconductor to form a heterostructure, in which the charge carriers can be efficiently separated due to the band bending and the formation of an internal electric field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Nevertheless, due to the high formation energy of Cs 2 AgSbBr 6 and considering the small ionic radius of Sb 3+ relative to Bi 3+ , synthesizing Cs 2 AgBiBr 6 powdered samples with a high level of Sb substitution is a challenging task. 47,52 In a single photocatalyst, rapid charge recombination is dominant because of the extraordinarily strong coulombic force between photogenerated electrons and holes, leading to low photoactivity. This issue can be addressed by coupling the material with another semiconductor to form a heterostructure, in which the charge carriers can be efficiently separated due to the band bending and the formation of an internal electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Sb incorporation leads to an asymmetric charge distribution that decreases the adsorption energy for methylbenzene and attracts benzylic hydrogen, efficiently reducing the C–H bond activation barrier, thus enhancing the photocatalytic methylbenzene conversion . Nevertheless, due to the high formation energy of Cs 2 AgSbBr 6 and considering the small ionic radius of Sb 3+ relative to Bi 3+ , synthesizing Cs 2 AgBiBr 6 powdered samples with a high level of Sb substitution is a challenging task. , …”
Section: Introductionmentioning
confidence: 99%
“…Although there are no serious toxicity concerns about the CABB precursors themselves, holding a mixture of concentrated HBr near its boiling point for several hours is quite delicate and poses severe dangers. Moreover, HBr as a solvent is limited as soon as the electronic properties, such as the bandgap energy, are tentatively varied by cationic substitution, for instance, by Sb 3+ substitution for Bi 3+ . These safety concerns even increase once large amounts of CABB absorber powders are required and the batch size is increased.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Smaller bandgaps have been reported in bulk powders and single crystals, with values as low as 1.55 eV reported. [27,28] Preliminary attempts have been made to investigate whether these reductions in bandgap could be translated into improvements in PV performance. However, groups have thus far reported that Sb alloying leads to a reduction in the PCE from >1% for Cs 2 AgBiBr 6 down to <0.3% for alloyed Sb-Bi elpasolite absorbers.…”
Section: Introductionmentioning
confidence: 99%